2003
DOI: 10.1046/j.1469-8137.2003.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of hyphae and roots to uranium uptake and translocation by arbuscular mycorrhizal carrot roots under root‐organ culture conditions

Abstract: Summary• Here, the respective contributions of the arbuscular mycorrhizal (AM) fungus Glomus intraradices and carrot ( Daucus carota ) roots to the uptake and translocation of uranium (U) were quantified and compared.• The U absorption by the AM fungus and roots was observed by growing mycorrhizal and nonmycorrhizal roots in two-compartment Petri plates. The central compartment allowed growth of roots and extraradical fungal hyphae. The external compartment (EC), which was labelled with 0.1 µ M 233 U, allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 36 publications
5
56
0
1
Order By: Relevance
“…Notably, the lowest percent Zn extracted was found in the AM roots at 250-[Zn], corresponding to the highest level of root colonization. These same trends can also be extrapolated from other phytoremediation studies (Davies et al 2001, Joner & Leyval 1997, Rufyikiri et al 2003, Wenger et al 2000. Based on our Zn removal yield results, additional studies are needed to assess the effectiveness of phytoextraction in soil remediation processes.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Notably, the lowest percent Zn extracted was found in the AM roots at 250-[Zn], corresponding to the highest level of root colonization. These same trends can also be extrapolated from other phytoremediation studies (Davies et al 2001, Joner & Leyval 1997, Rufyikiri et al 2003, Wenger et al 2000. Based on our Zn removal yield results, additional studies are needed to assess the effectiveness of phytoextraction in soil remediation processes.…”
Section: Discussionmentioning
confidence: 52%
“…Despite this, it has been suggested that AM fungi may eliminate the bioavailability of otherwise toxic contaminants and consequently buffer the soil for plants and other microorganisms (Joner et al 2000). By contrast, Davies et al (2001Davies et al ( , 2002 and Rufyikiri et al (2002Rufyikiri et al ( , 2003 showed, respectively, colonization by G. intraradices enhanced uptake and accumulation of chromium in sunflower and of uranium in cultivated in vitro carrot roots by G. intraradices. Although AM fungi may enhance heavy metal phytoextraction for some plant species, our findings agree with the hypothesis of metal-binding AM fungal capacity as suggested by others (Chen et al 2001, Joner et al 2000, Li & Christie 2000.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, at higher pH, and especially at pH 8, the major U species in solution were neutral or negatively charged. Nonetheless, at pH 5.5, Rufyikiri et al (2003) observed that Cu-extractable U represented 15% of the U content of the fungal mycelium, and that further extraction with HCl desorbed 67% of U (200 mg fresh roots and 20 mg fresh extraradical mycelium were equilibrated for 3 h with 15 ml and 5 ml of a solution containing 10 À2 M CuSO 4 and then with 10 À1 M HCl). Finally, possible adsorption of U on intracellular membranes is also to be excluded as cytoplasmic pH was probably near neutral and vesicular or vacuolar pH is slightly acidic (Rasmussen et al, 2000;Saito et al, 2004).…”
Section: Effect Of Phmentioning
confidence: 99%